Practical Pelvic Floor Ultrasonography A Multicompartmental Approach to 2D/3D/4D Ultrasonography of Pelvic Floor - Shobeiri, S. Abbas (Springer New York : Imprint: Springer, 2014)
Practical Pelvic Floor Ultrasonography: A Multicompartmental Approach to 2D/3D/4D Ultrasonography of Pelvic Floor provides an introduction to pelvic floor imaging, as well as a resource to be used during initial and more advanced practice. The book helps readers gain competence in performing 2D/3D/4D transperineal, and 2D/3D endovaginal / endoanal ultrasound evaluation of the pelvic floor, including anal sphincter and levator ani complex. The text also shows interested clinicians how to obtain optimal images of pelvic floor muscles and organs, how to obtain useful images of the anal canal, levator ani complex, urethra, and how to interpret clinical implications of alterations of the anatomy. In addition, emerging techniques of "dynamic" pelvic floor ultrasound and 3D/4D ultrasound are introduced through step by step protocols that are aimed at optimizing sonographic images. Written entirely by experts in their fields, Practical Pelvic Floor Ultrasonography: A Multicompartmental Approach to 2D/3D/4D Ultrasonography of Pelvic Floor is a comprehensive resource that will be of great value to urogynecologists, colorectal surgeons, obstetrician and gynecologists, female urologists, ultrasonographers, radiologists, physiotherapists, as well as fellows in urogynecology and colorectal surgery.